Expression Pattern, Regulation, and Biological Role of Runt Domain Transcription Factor, run, in Caenorhabditis elegans - Nam, Seunghee (American Society for Microbiology, 2002)
The Caenorhabditis elegans run gene encodes a Runt domain factor. Runx1, Runx2, and Runx3 are the three known mammalian homologs of run. Runx1, which plays an essential role in hematopoiesis, has been identified at the breakpoint of chromosome translocations that are responsible for human leukemia. Runx2 plays an essential role in osteogenesis, and inactivation of one allele of Runx2 is responsible for the human disease cleidocranial dysplasia. To understand the role of run in C. elegans, we used transgenic run::GFP reporter constructs and a double-stranded RNA-mediated interference method. The expression of run was detected as early as the bean stage exclusively in the nuclei of seam hypodermal cells and lasted until the L3 stage. At the larval stage, expression of run was additionally detected in intestinal cells. The regulatory elements responsible for the postembryonic hypodermal seam cells and intestinal cells were separately located within a 7.2-kb-long intron region. This is the first report demonstrating that an intron region is essential for stage-specific and cell type-specific expression of a C. elegans gene. RNA interference analysis targeting the run gene resulted in an early larva-lethal phenotype, with apparent malformation of the hypodermis and intestine. These results suggest that run is involved in the development of a functional hypodermis and gut in C. elegans. The highly conserved role of the Runt domain transcription factor in gut development during evolution from nematodes to mammals is discussed.